The early history of freshwater fish production and consumption in Thailand - Edwards, Peter (Frontiers in Aquaculture, 2023)
The history of freshwater fish production and consumption in Thailand were reviewed in the late 1970s. While aquaculture had a history of more than a century in the country it had only started to expand relatively recently because of the abundance of wild fish in former times. Historical aspects of freshwater capture fisheries and freshwater aquaculture in Thailand, and the development of irrigation in Central Thailand which played an important role in facilitating the development of inland aquaculture in the country were reviewed. While dam construction led to the demise of the flood plain capture fishery, it provided a controlled water supply necessary for the subsequent development of aquaculture. The study informed the development of education and research in aquaculture at the Asian Institute of Technology (AIT). More recent developments in Thai aquaculture are outlined. Malnutrition in developing countries and fish in the Thai diet at the time of the study were also reviewed.